2020
DOI: 10.3390/molecules25112618
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protective Agents for The Freeze-Drying of Paenibacillus polymyxa Kp10 as a Potential Biofungicide

Abstract: Anthracnose is a fungal disease causing major losses in crop production. Chemical fungicides widely used in crop plantations to combat fungal infections can be a threat to the environment and humans in the long term. Recently, biofungicides have gained much interest as an alternative to chemical fungicides due to their environmentally friendly nature. Biofungicide products in powder form can be formulated using the freeze-drying technique to provide convenient storage. Protective agent formulation is needed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The response surface design method is an effective method to establish the correlation between multiple variables. As demonstrated in the previous studies, the response surface design method could successfully optimize the freeze-dried powder formulation (Nasran et al, 2020;Shu et al, 2019). Directed vat set starter is a highly concentrated and standardized starter strain with high fermentation efficiency.…”
mentioning
confidence: 88%
“…The response surface design method is an effective method to establish the correlation between multiple variables. As demonstrated in the previous studies, the response surface design method could successfully optimize the freeze-dried powder formulation (Nasran et al, 2020;Shu et al, 2019). Directed vat set starter is a highly concentrated and standardized starter strain with high fermentation efficiency.…”
mentioning
confidence: 88%
“…However, drying of mRNA-LNPs is more sophisticated as the freezing and the dehydration process induces mechanical force and deforms the vehicle structure, leading to vehicle aggregation, mRNA breakage, or leakage 24,25 . Some studies have shown that although mRNA-LNPs maintain their integrity and encapsulation efficiency, the in vivo uptake efficacy is greatly reduced after lyophilization due to some unknown reasons 15,[26][27][28][29] . In addition, the reported studies regarding mRNA-LNPs lyophilization mostly focus on the maintenance of its biological activity, while there are few studies on the lyophilization procedures 30 .…”
Section: Introductionmentioning
confidence: 99%
“…They are not resistant to the influence of physical environmental factors, die quickly, and are demanding to the cultivation conditions. Therewith, if cultivation and storage conditions are not observed, bacteria lose their virulence, which reduces their scientific value for researchers and practical use (Nasran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%